A green public transportation system using E-buses: A technical and commercial feasibility study. (November 2019) - Majumder, Suman; De, Krishnarti; Kumar, Praveen; Rayudu, Ramesh
Highlights: A sustainable public transportation system has been proposed here for Guwhati city. The proposed system utilizes high capacity battery (HCB) and supercapacitor to drive the E-buses using electric energy. The faster charging and discharging capability of supercapacitors makes it suitable for city traffic conditions of overcrowded Indian cities. The unique feature of the proposed system is it does not put extra burden on grid. The HCB also facilitates the use of renewable sources of energy for supporting the proposed system. Abstract: Economic growth in the emerging countries has led to rapid urbanization and expansion of existing cities. As a result, major cities in the emerging nations experience traffic congestion and deteriorating air quality. One of the solutions to overcome these problems is to develop a comprehensive public transportation system based on clean fuel. This work proposes a public transportation system based on electric buses that can be used in the cities. Here, the proposed system is studied and analyzed for Indian scenario. High capacity batteries and distributed solar PV generation has been used to ensure that no additional burden is put on the existing distribution network. These batteries are placed at each bus stop to store energy from the grid during the off-peak hours, and the supercapacitor in the buses will be flash charged from these batteries. In this work, the architecture of the proposed system has been presented along with initial sizing of the subsystems, for understanding the operation of the system for various scenarios, and to investigate its interaction with the grid. The results show that such a system, if carefully designed, is feasible and is capable of meeting the transportation needs without adding additional burden to the grid.